Different methods of training load quantification and their relationship to injury and illness in elite Australian football. Issue 1 (January 2016) - Veugelers, Kristopher R.; Young, Warren B.; Fahrner, Brendan; Harvey, Jack T.
Abstract: Objectives: To compare different methods of training load (TL) quantification and their relationship to injury and illness in elite Australian footballers. Design: Prospective cohort study. Methods: Forty-five elite Australian footballers (mean ± standard deviation: age = 23.4 ± 3.8 years) from one elite club participated in this 15 week pre-season study. TL was quantified every session for each individual using four different methods involving rating of perceived exertion (RPE). Two of these methods enabled the quantification of TL for all exercise modalities whilst two were applicable only to outdoor field activities. One- and two-weekly cumulative TL was investigated against injury and illness data using a logistic regression model where the low TL group was considered as the reference group. Results: A general trend existed across all TL methods which suggested lower odds of injury and illness in high TL groups. The one-week RPE (all) and one-week RPE x Duration (all) methods detected reduced odds of injury in high TL groups compared to low TL groups ( p < 0.05, OR = 0.199–0.202). Similarly, the one-week RPE (field) method identified lower illness odds in the high TL groups ( p < 0.05, OR = 0.083–0.182). Conclusions: Higher TL appeared to provide a protective effect against both injury and illness. The inclusion of duration in the quantification of TL via RPE did not improve the ability of RPE to predict change in odds of injury or illness.